(untitled) (Journal of Economic Research & Business Administration, 2016)
This article presents vertical spread.This article is about financial op tions. For call options in general, see Option (law). A call option, often simply labeled a call , is a financial contract between two parties, the buyer and the seller of this type of option The characteristics of call and put options as exchange-traded instru ments and their different combinations to achieve the investment objec tive. For this opredelnie concept of “Option Strategy” and describes the basic strategy options: Long Straddle and Short Straddle, Long Strangle Short Strangle and to determine their benefits. Transactions are made for buying and selling options. There are two types of options Call and Put and important to look at from the point of view, both the buyer and the seller. Options give the chance to earn profit with the help of speculation, and to hedge risks associated with fluctua tions in the price.